2019
DOI: 10.1177/1078155219868761
|View full text |Cite
|
Sign up to set email alerts
|

Current status of eye disorders caused by docetaxel administration every 3 weeks: A case-control study in Japanese patients

Abstract: Purpose Docetaxel is known to cause eye disorders. In this study, current status of eye disorders caused by docetaxel administration every 3 weeks in Japanese patients was examined. Methods This case-control study targeted patients who were newly administered docetaxel at the Kyoto Okamoto Memorial Hospital between 1 July 2015 and 30 June 2018. Eye disorder occurrence was defined as an event in which the pharmacist confirmed the symptoms in a patient interview and the ophthalmologist diagnosed the disorder. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The median value of the cumulative dose was 291.0 (42.3-937.4). In previous trials, the multivariate regression analysis revealed that a higher cumulative dose was significantly associated with the presence of epiphora [14,27], and that a higher dose was significantly associated with the canalicular stenosis [14].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The median value of the cumulative dose was 291.0 (42.3-937.4). In previous trials, the multivariate regression analysis revealed that a higher cumulative dose was significantly associated with the presence of epiphora [14,27], and that a higher dose was significantly associated with the canalicular stenosis [14].…”
Section: Discussionmentioning
confidence: 87%
“…The inclusion criteria were met by 10 trials, from which one was excluded owinf to data selection biases. Accordingly, nine studies [7,14,25,[27][28][29][30][31][32] were evaluated quantitatively and qualitatively in our review (Table 1). From the eligible trials, a total of 456 women were included in the analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Docetaxel is a member of taxanes and inhibits mitosis in dividing cancer cells by preventing microtubule depolymerization and attenuating the effects of bcl-2 and bcl-xL expression [ 38 , 39 ]. It frequently causes canalicular and nasolacrimal duct obstruction, with resulting epiphora [ 40 , 41 ]. Docetaxel is secreted in the tear film, which results in canalicular chronic inflammation and is thought to be the cause of canalicular stenosis.…”
Section: Reviewmentioning
confidence: 99%
“…Epiphora may interfere with daily life activities and consists a troublesome symptom for patients. The use of lubricant eye drops may help wash out docetaxel and prevent dacryostenosis [ 40 , 41 ]. Docetaxel also rarely causes cystoid macular edema and erosive conjunctivitis [ 40 , 42 , 43 ].…”
Section: Reviewmentioning
confidence: 99%